Localizing conditional clauses in the left periphery - Munaro, Nicola (Linguistica (Ljubljana), 2016)
This article analyzes the distribution of conditional clauses in multiple complementizer constructions, showing that preposed adverbial clauses could occupy in early Italo-Romance varieties different specifier positions within the left periphery of embedded clauses, a possibility that has been lost with time in Italo-Romance but is still attested in modern Ibero-Romance. It is further argued that in multiple complementizer structures the highest complementizer invariably lexicalizes the head Force°, while the other occurrences of the complementizer mark the lower boundary of the main two Topic subfields.
Keywords: conjonction; langues romanes; pogojni odvisnik; romanski jeziki; sintaksa; skladnja; subordonnée de condition; syntax; syntaxe; veznik